2010
DOI: 10.1073/pnas.1006007107
|View full text |Cite
|
Sign up to set email alerts
|

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis

Abstract: Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The improved NK1 mutants described here could support further development of other Met agonists that are comprised partially or wholly from the unstable wild-type NK1 fragment (33)(34)(35), and given their enhanced stability have potential to be readily incorporated into biomaterials for therapeutic applications (36). In addition, these engineered NK1 agonists and antagonists will be important tools for further elucidating determinants of Met binding and activation.…”
Section: Stability Engineering and Relationship To Soluble Expressionmentioning
confidence: 85%
“…The improved NK1 mutants described here could support further development of other Met agonists that are comprised partially or wholly from the unstable wild-type NK1 fragment (33)(34)(35), and given their enhanced stability have potential to be readily incorporated into biomaterials for therapeutic applications (36). In addition, these engineered NK1 agonists and antagonists will be important tools for further elucidating determinants of Met binding and activation.…”
Section: Stability Engineering and Relationship To Soluble Expressionmentioning
confidence: 85%
“…The biological data accumulated for the NK1 molecule led most investigators to consider this structure as the minimal unit for MET agonist design. Indeed, several NK1 derivatives having either altered HS binding properties 25 , 27 or improved dimeric stability 28 , 29 were produced with the goal to promote tissue diffusion capacities and MET agonistic potential. A similar strategy was applied for the design of a MET antagonist with potential applications in cancer targeted chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, amino acid scarcity which increases lifespan, acts through the Tor/Sch9 pathway [37], and amino acid withdrawal and repletion studies point to the TORC1 complex as a major amino acid transducer in mammalian cells [38, 39] which include the essential amino acids, leucine and methionine and to a lesser extent the non-essential amino acid arginine [40]. In yeast, we recently showed that methionine restriction does not extend lifespan and instead threonine and valine can promote stress sensitization by activating the mTOR pathway.…”
Section: Cr and Protein/amino Acid Restrictionmentioning
confidence: 99%